(untitled) (Editora Impacto Científico, 2025)
This article aims to report and discuss the Conversation Circles held with the residents mobilized for the realization of the mini-food factory, in a peri-urban area, close to the Integrated Center for Education and Culture, CIEC, in the city of Barbalha, Ceará, with a view to improving family income. Workshops were held, all with the methodology of the Conversation circle on the following topics: Food waste and damage to the environment and Citizenship, rights and duties and community participation. It was concluded that the Conversation Circles fulfilled the role of mobilizing and raising awareness among residents about the need for collective projects aimed at local social and economic development, as well as the need for community political participation, with a view to the common good and human enrichment, and also that Conversation Circles are a liberating political strategy, that favors the human, political and social emancipation of historically excluded collectives. From the researcher’s observation and the help of the recorded material, it was possible to verify that the objective of the conversation circles was fulfilled, since the invited subjects, at the end of the process, that is, after the workshops in the format of conversation circles, were sensitized and open to participation and work in the mini-food factory and to learn how to manage the enterprise. The interaction of the group participants with the researcher and of the participants with themselves were very positive. It can be said that there was an "empowerment", especially of women, in relation to the initiatives within the project, which demonstrates that taking the word before the project and building the project to get bread (paraphrasing Selvino Heck) can be an appropriate strategy in the implementation of social projects, mainly aimed at cooperative entrepreneurship. DOI: https://doi.org/10.56238/edimpacto2025.090-012